Kontribusi Keteladan Guru PAK Bagi Pembentukan Spritualitas Dan Karakter Siswa di Era Disrupsi Dunia - Kemryati Juleha Siburian; Dorlan Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
PAK teachers not only act as resource persons in the learning process, but more than that is to provide good examples as their contribution to shaping the spirituality and character of students. The purpose of this study is to find out how the contribution of PAK teachers in schools to the formation of spirituality and student character in the era of disruption. The research method used in this research is a qualitative method with a literature study approach. The author collects and analyzes information from various literatures such as books, journals and other scientific articles and draws conclusions. The success of a PAK teacher in the formation of spirituality and student character starts from himself by becoming a role model both in terms of spirituality, intellectual, moral and social aspects.